Study of the features of digitalization of the heat supply system of the city of Bukhara - Rashid B. Jalilov; Umar U. Kamalov; Anvar T. Karaev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: due to the need to introduce digitalization in heat supply systems. Inefficient use of energy resources in existing heating networks is associated with significant energy losses in outdated heat supply systems. It is substantiated that digitalization and the transition to modern, closed heat supply systems with the installation of individual heating points (IНP) will ensure a significant reduction in losses, and ultimately lead to a more rational use of energy resources. Aim: to increase the efficiency of energy use in heat supply systems, ensure significant savings in thermal energy, reduce the costs of generation, transportation, distribution and regulation of heat supplies, as well as the introduction of more rational metering of thermal energy for consumers. Methods: replacement of existing and outdated heating systems with modern ones with the introduction of digitalization and the transition to closed heat supply systems with the installation of individual heating points (IНP), as close as possible to the consumer. Results: increased efficiency in the use of energy resources, significant savings in thermal energy, reduced costs for heat generation, reduced losses in heat supply systems, reduced costs for equipment maintenance and repair, and more rational and accurate accounting of thermal energy consumption for consumers.